New York : The Novel - Rutherfurd, Edward (New York : Doubleday, 2009)
A tale set against a backdrop of New York City's history from its founding through the September 11 attacks traces the experiences of characters who witness such periods as the Revolutionary War, the city's emergence as a financial giant, and the Gilded Age.
Keywords: New York (N.Y.) -- Fiction -- History; Fiction